Public administration : understanding management, politics, and law in the public sector - Rosenbloom, David H. 4 0 16; Kravchuck, Robert,;Clerkin, Richard M.; 5 (Boston : McGraw-Hill, 2009)
Public Administration: Understanding Management, Politics, and Law in the Public Sector ground students in the fundamentals of public administration while embracing its complexities through multiple sets of values that affect administration management of the American state.--BOOK JACKET.
Introduction : definitions, concepts, and setting -- The practice and discipline of public administration : competing concerns -- The American administrative state : development and political environment -- Federalism and intergovernmental relations : the structure of the American administrative state -- Core functions -- Organization : structure and process -- Public personnel administration and collective bargaining -- Budgeting and the public finances -- Decision making -- The convergence of management, politics, and law in the public sector -- Policy analysis and implementation evaluation -- Regulatory administration : an illustration of management, politics, and law in the public sector -- Public administration and the public -- Public administration and the public -- Public administration and democratic constitutionalism -- Accountability and ethics -- The future.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Public administration. -- 20; Politics and government. -- United States -- 20; 2